China’s modernization, rural regeneration and historical agency (Argumentum, 2014)
Like most of the once down-trodden colonized nations, China’s key historical project of the last 150 years has been to enforce modernization. The aim and mechanism of modernization has generally been simplified as industrialization, a process China has pursued since the mid-19th century. Wen Tiejun portrays China’s development in the last 150 years as ‘the four phases of industrialization of a peasant state’ with the ultimate aim of becoming a powerful modern state to counter European and Japanese imperialism, and later the United States’ embargo during the Cold War. The first attempt was the Yang Wu Movement initiated by the Qing dynasty from 1850 to 1895; the second the industrialization policy pursued by the Republican government from 1920s to the 1940s; the third the “state primitive accumulation of capital” practiced by the Communist Party regime from the 1950s to the 1970s; and the fourth the reform and open-door policy promoted by Deng Xiaoping since the late 1970s (Wen 2001). There has been intellectual consensus on modernization calling out for radical social reform in China in the 20th century. Since the 1920s all major intellectual thought has been in agreement that China needs a thorough social overhaul. The only difference was whether the model should be American capitalism or Russian socialism. Among these radical ideas and social programs, the rural reconstruction movement during the 1920s-30s represented by Liang Shuming and James Yen was a social initiative that was much neglected. It is of particular relevance to reconsider this intellectual heritage in post-development China. We will turn to this later in this essay.